PENGARUH MODEL PEMBELAJARAN ROLE PLAYING BERBANTUAN MEDIA VIDEO TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SDS PELITA KASIH KOTA SINGKAWANGDUL ARTIKEL PENELITIAN - Novania; Dina Anika Marhayani; Dodik Kariadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: 1) Determine the influence of the Role Playing learning model assisted by video media on the learning outcomes of Pancasila Education students in grade V of SDS Pelita Kasih. 2) To find out how much the influence of the Role Playing model assisted by video media on the learning outcomes of Pancasila Education students in grade V of SDS Pelita Kasih. The research used was a pseudo-experimental research with a One Group Pre-Test Post-Test design. The population in this study is all grade V students of SD Private Pelita Kasih Singkawang which consists of 1 class with a total of 23 students. The sampling technique in this study is Nonprobability Sampling for all students in class V totaling 23 students. The prerequisite test carried out was a normality test using the Shapiro-Wilk formula and a variant homogeneity test was carried out to see the similarity of variants in both groups. The data were analyzed univariately with a significance level of 5% (0.05) for the first hypothesis test using a t-test. The results of the study show that: 1) From the calculation of student learning outcomes between before and after using the Role Playing learning model assisted by video media on the learning outcomes of Pancasila Education students in grade V of SDS Pelita Kasih. This is evidenced by the Independent Sample t-test using SPSS Version 26 in a sig value. (2-tailed) < 0.05, which is 0.000 < 0.05. 2) The Role Playing learning model has a great influence on the video media-assisted learning outcomes of Pancasila Education students in grade V of SDS Pelita Kasih. This is evidenced by the effect size test obtained a value of 2.565 with a high category.